Prevalence, pattern and attitude towards self-medication practice for dental problems in Kuantan, Pahang - Ismail, Azlini; Abllah, Zurainie; Abdul Majid, Muhammad Nazmi; Mohd Haron, Muhammad Nabil (2021)
This PDF contains 37-pages of slides which has been prepared by the inventor and co-inventors while participating in the 9th Dental Students’ Scientific Conference, on 28th February 2020.